La desintegración familiar en el desarrollo socio afectivo de los niños de 4 a 5 años de Educación Inicial. - Calvache Quintana, Gabriela María (2020)
Family disintegration mainly affects the child's socio-emotional development, leading to behavioral problems such as low self-esteem, violent behavior towards the whole world, school failure, then the problem develops and grows from the child's emotional world. As for the interest lies in providing timely and effective information and guidance on the incidence of family disintegration in the socio-emotional development of the child from his emotional, communicative psychological needs that tend to break the fraternal ties between father and son. Around the above, the study is useful, because it will allow emotional support to affected children from the educational context, as well as to inform parents of the causes and consequences that lead to family breakdown and how it affects to the socio-emotional development of children in their integral formation. From this point of view, the objective of the investigation was to determine the incidence of family disintegration in the socio-affective development of children from 4 to 5 years of Initial Education of the Republic of Colombia School, La Matríz Parish, Saquisilí Canton, Cotopaxi Province. To comply with it, field research is carried out, such as the survey of parents, direct observation of children in the educational center. The bibliographic and field research as well as the exploratory and descriptive research were used for theoretical support. As for the direct beneficiaries, the children and parents of the Educational Institution were the reason for the investigation.